Analysis of the Implementation of As-Salam Contract in White Garlic Purchase Transactions between Retailers and Distributors: Case Study White Garlic Industry Supply Chain in Medan City - Siregar, Choirussonya Putri Amini; Anggraini , Tuti; Harahap, Muhammad Ikhsan (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the application of the As Salam contract in the purchasing system of garlic between retail traders and importers in Medan, Indonesia. Research Methodology: The research utilizes a qualitative approach, employing observation and structured interviews with key participants in the garlic trading industry. The instruments include interview guides and observational checklists to gather detailed insights into the contract negotiation and execution process. Results: The findings indicate that the trading practice involves detailed contract agreements, including specific terms on quantity, quality, and delivery schedules. The principles of the As Salam contract are strictly adhered to, ensuring clarity and minimizing the potential for disputes. Prepayment is an integral part of the contract, facilitating efficient stock planning and delivery logistics. Limitations: The study is limited to the garlic trade within the Medan region, which may restrict the broader applicability of the findings to other commodities or regions. Contribution: This research contributes to the discipline of Islamic economics by providing practical insights into the implementation of As Salam contracts in commodity trading, offering a model for ensuring fairness and transparency in accordance with Islamic law.